Effect of Patchouli oil Against the Death Time Brown Dog Ticks - Risna Wati; Muh. Nur Amir; Isra Wahid; Adryani Ris; Baso Yusuf (Hasanuddin University, 2021)
Patchouli oil is an essential oil derived from the patchouli plant, and it has many benefits, including the insecticide effect. Rhipicephalus sanguineus tick is a parasite often found in dogs in Indonesia. This study aims to determine the effect of patchouli oil on the mortality of R. sanguineus ticks in dogs. Samples of this study were 25 R. sanguineus ticks, and they were divided into five treatments: positive control, negative control, 5% patchouli oil, 10% patchouli oil, 20% patchouli oil. The result of this study showed that all ticks in the negative control using hexane were found alive. All ticks in the positive control using Ivermectin were found dead. Ticks in 5% patchouli oil showed that 4 of 5 ticks were found dead. Ticks in 10% and 20% patchouli oil showed that 5 of 5 ticks were found dead. This study conclude that patchouli oil can be used as an insecticide and 20% patchouli oil concentration has statistically no significant difference from the positive control. Moreover, this study suggests using patchouli oil as an alternative insecticide due to its low price compared to Ivermectin.